The Chief Concern of Medicine : The Integration of the Medical Humanities and Narrative Knowledge into Medical Practices - Schleifer, Ronald; Crow, Sheila; Vannatta, Jerry (Book collections on Project MUSE., 2013)
Unlike any existing studies of the medical humanities, 'The Chief Concern of Medicine' brings to the examination of medical practices a thorough - and clearly articulated - exposition of the nature of narrative. The book builds on the work of linguistics, semiotics, narratology, and discourse theory and examines numerous literary works and narrative "vignettes" of medical problems, situations, and encounters. Throughout, the book presents usable expositions of the ways storytelling organizes itself to allow physicians and other healthcare workers (and even patients themselves) to be more attentive to and self-conscious about the information - the "narrative knowledge" - of the patient's story.